2019
DOI: 10.1108/jhr-08-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of modified health belief model-based intervention to reduce body mass index for age in overweight junior high school students in Thailand

Abstract: Purpose The purpose of this paper is to determine the effectiveness of a modified HBM-based intervention to reduce body mass index (BMI) for age in overweight junior high school students. Design/methodology/approach A cluster-randomized controlled trial was conducted in the first and second years of a junior high school in the center of Thailand. In total, 24 classrooms were randomly assigned to a modified health belief model intervention arm (HBMIA), and 24 classrooms were randomly assigned to a traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
5
2
2
Order By: Relevance
“…The sixth finding showed that perceived benefit of functional food related to COVID-19 did not significantly influence males' functional food loyalty. This finding was poles apart with the proposition of the HBM [29]. This finding was also different from the findings of the previous studies [58], [59].…”
Section: Theoretical Implicationscontrasting
confidence: 99%
See 2 more Smart Citations
“…The sixth finding showed that perceived benefit of functional food related to COVID-19 did not significantly influence males' functional food loyalty. This finding was poles apart with the proposition of the HBM [29]. This finding was also different from the findings of the previous studies [58], [59].…”
Section: Theoretical Implicationscontrasting
confidence: 99%
“…The fifth finding of this research found that perceived threat of COVID-19 did not significantly influence males' loyalty toward males' functional food loyalty during the COVID-19 pandemic. This finding was a deviation from the HBM, which proposed that the perceived threat of disease positively influenced health behaviour [29]. This finding was also in contrast with finding of the previous studies [58], [59].…”
Section: Theoretical Implicationscontrasting
confidence: 86%
See 1 more Smart Citation
“…7 Sağlık İnanç Modeli'nin obeziteyi etkin bir şekilde yönetebilmek için değiştirilebilir faktörler üzerinde etkinliği kanıtlanmıştır. 19,20…”
Section: Obezite Yönetimiunclassified
“…As 10 (dez) tecnologias educativas disponíveis como programas escolares tem características de intervenções multicomponente desenvolvidas a longo prazo. A ancoragem de uma abordagem para toda escola tem sido utilizada para implementação dos programas escolares para adoção de estilos de vida saudáveis de adolescentes por conseguir envolver diversos agentes da comunidade educativa (Khumros, et al, 2018;kolbe, 2019).…”
Section: Programa Escolarunclassified